Exploring students' views and preferences in teachers' comments - Canilao, Paz N. (Tanglaw: official journal of the College of Education, 2004)
In the last three decades, writing experts have argued for the usefulness of comments on students' paper to promote successful writing. Feedback gives the students direction in the revision process; it helps the students to make decisions on the kind of changes that must be made in order for their papers to work. This research discusses the views and preferences that students have with regard to teacher comments. The results of a survey given to a group of DLSU students show that the students generally have a positive attitude towards teacher comments and that they prefer a combination of conversational and telegraphic comments on their writing. This article also discusses the implications of these views and preferences for classroom instruction.